Longitudinal trajectory and predictors of change in family accommodation during exposure therapy for pediatric OCD. (October 2021) - Jacoby, Ryan J.; Smilansky, Hannah; Shin, Jin; Wu, Monica S.; Small, Brent J.; Wilhelm, Sabine; Storch, Eric A.; Geller, Daniel A.
Highlights: FA changed significantly during treatment, with gains maintained over 6-months. Baseline OCD symptom severity did not predict changes in FA. Children with higher baseline impairment exhibited greater improvements in FA. Therapeutic alliance and treatment expectancies did not predict changes in FA. FA mediated relationship between OCD symptom severity and parent-rated impairment. Abstract: Family accommodation (FA) is key in the maintenance of OCD. However, most studies are cross-sectional, and have not identified long-term trajectories and correlates of FA changes over treatment. This study investigated changes in clinician-rated FA over 10 sessions of cognitive behavioral therapy (CBT) for 142 children with OCD, as well as several key predictors/correlates: (a) clinician-rated OCD symptom severity, (b) child- and parent-rated functional impairment, (c) parent-rated treatment expectancies, and (d) child- and parent-rated therapeutic alliance. Multi-level models indicated that FA changed significantly during treatment, with gains maintained over 6-months. Baseline clinician-rated OCD severity did not predict changes in FA. Significant interactions indicated that children with higher child- and parent-rated impairment exhibited greater FA improvements over treatment (versus children with lower impairment). Child- and parent-rated therapeutic alliance and parent-rated expectancies did not predict FA changes. Finally, FA mediated the relationship between OCD severity and parent- (but not child-) rated impairment. Reverse mediation models were also significant. Findings indicate that CBT can successfully reduce FA (a) even if children experience high OCD severity and interference in school, relationships, and family life, and (b) regardless of non-specific factors like treatment expectancies and alliance. FA reductions are an important mechanism mediating treatment response.